GAMBARAN MINAT IBU DALAM MEMILIH KB IMPLAN DI DESA KARANG NANGKA KECAMATAN RUBARU KABUPATEN SUMENEP - Iva Gamar Dian Pratiwi; Emdat Suprayitno; Anita Novi Kristanti (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2018)
The problem raised in this study was that the low coverage of Implant KB in Karangnangka Village in 2014 was only 5 people while the target to be achieved was 18 people. The low coverage of implantable family planning in Karangnangka Village, Rubaru District is caused by several factors, namely internal factors and external factors. This study aims to determine the description of the interests of mothers in choosing KB Implants in Karangnangka Village, Rubaru District, Sumenep Regency in 2014.This study uses descriptive research. Total sample of 204 respondents. Data acquisition was obtained using a questionnaire sheet. The data analysis technique used in this study is distributionfrequency. To calculate the results of data processing using the SPSS programfor Windows. The results showed that the majority of respondents aged between 26-35 years were as many as 106 respondents (52%). Most of the respondents' education was only at the elementary school level, which was 172 respondents (84.3%). Most of the respondent's work as a farmer is 191 respondents (93.6%), and the number of respondent's children is mostly 1 (one) and 2 (two). While the description of the interest of mothers in choosing Implant KB included low interest as many as 137 respondents (67.20%). While the acquisition of scores of factors that affect the low interest of mothers in choosing the implant KB based on internal needs is 436 (47.65%), social motives 339 (37.05%) and emotional 140 (15.30%). Based on the results of the study it can be concluded that the description of the interest of mothers in choosing implantable family planning in Karangnangka Village, Rubaru Subdistrict is mostly included in the low interest category. The factors that most influence the interest of mothers in choosing implantable family planning are internal needs. Therefore, health workers provide education (socialization) to the community, especially mothers about the benefits of contraception so that the interest of mothers in choosing implant KB is higher.